2021
DOI: 10.1002/tkm2.1274
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of 120 types of herbal extracts and their effects on morphology in cultured neuronal or glial cell lines, followed by RNA extraction for a cDNA library: Consideration for use in studies based on Kampo theories

Abstract: Aim Kampo medicine is composed of a variety of crude drugs. Each crude drug has its own effects, and the interaction of all drugs produces the therapeutic effect of Kampo medicine. In order to examine the characteristics of Kampo medicine and its crude drugs, 120 types of herbal medicines were characterized based on their three‐dimensional high‐performance liquid chromatography (3D‐HPLC) profiles as well as their effects on cell morphology/proliferation when added to cultured cells and gene expression changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“… Note : The data in this table were extracted from our previously reported findings [11]. The top shows the results from C6 and the bottom from N18.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… Note : The data in this table were extracted from our previously reported findings [11]. The top shows the results from C6 and the bottom from N18.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that RNA was extracted from a cultured neuronal cell line N18TG‐1 (N18) and glial cell line C6Bu‐1 (C6) treated with 120 kinds of herbal extracts which were supplied by the Institute of Natural Medicines (INM), University of Toyama, Japan. Using these RNAs, a cDNA library was prepared [11]. Furthermore, using the cDNA library, we also examined all of the 120 crude drug extracts from the overall perspective to determine which herbal drugs are involved in BNIP‐3 mRNA changes [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors created a cDNA library for the purpose of examining the gene expression effect of 120 kinds of crude drugs alone [2], and are proceeding with various experiments on the components' cytotoxicity, function, and gene expression. In the process, we observed a mysterious phenomenon related to CR and RR.…”
Section: Introductionmentioning
confidence: 99%